Safety and Efficacy of Early Rehabilitation After Stroke Using Mechanical Thrombectomy: A Pilot Randomized Controlled Trial - Wang, Wei; Wei, Ming; Cheng, Yuanyuan; Zhao, Hua; Du, Hutao; Hou, Weijia; Yu, Yang; Zhu, Zhizhong; Qiu, Lina; Zhang, Tao; Wu, Jialing (Frontiers in Neurology, 2022)
Background Early rehabilitation (ER) has been reported to be both safe and feasible for patients post-stroke. To date, however, ER-related outcomes concerning patients who have undergone mechanical thrombectomy (MT) have not been investigated. This study aimed to determine the feasibility of ER and whether ER improves prognosis in such patients. Methods In this single-center, double-blinded, randomized controlled study involving 103 patients who met the study MT criteria, we randomly divided patients (1:1) into ER and conventional rehabilitation groups. The primary outcome was mortality; secondary outcomes included favorable outcomes (modified Rankin scale, 0–2), the incidence of non-fatal complications, and Barthel Index (BI) scores. We assessed outcomes at 3 months and 1 year. Results No significant between-group differences were found in terms of mortality and favorable outcomes at 3 months and 1 year post-stroke. At 3 months, 15 (28.8%) patients had non-fatal complications in the ER group and 29 (56.9%) in the conventional rehabilitation group (P = 0.002). The BI in the ER and conventional rehabilitation groups was 100 (85–100) and 87.5 (60–100), respectively, (P = 0.007). At 1 year, the incidence of non-fatal complications was similar between both groups (BI in the ER group, 100 [90–100], P = 0.235; BI in the conventional rehabilitation group, 90 [63.8–100]; P = 0.003). Conclusions ER reduces the incidence of early immobility-related complications and effectively improves patients’ activities of daily living on a short- and long-term basis. Our results indicate that MT contributes to ER in patients with stroke.